2012
DOI: 10.1016/j.farma.2011.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the use of clopidogrel associated with gastroprotective medications in outpatients

Abstract: In our study, we did not evaluate the clinical status of the patients and the rates of reinfarction. And, as our study data showed, there are not any statistically differences between the groups that used clopidogrel associated with omeprazole, with ranitidine or that did not use any gastroprotective medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…A total of 12 studies containing 3,301 patients (2,068 in the PPIs group, 1,233 in H 2 RAs group) were included in the analysis. 13 24 The risk of bias for all included RCTs is high except the low risk of bias for Furtado et al 14 and moderate risk of bias for Ng et al 16 For cohort studies, the risk of bias for Cappelletti Galante et al, 21 Ng et al 23 and Yew et al 24 is moderate and the risk of bias for Macaione et al 22 is high.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…A total of 12 studies containing 3,301 patients (2,068 in the PPIs group, 1,233 in H 2 RAs group) were included in the analysis. 13 24 The risk of bias for all included RCTs is high except the low risk of bias for Furtado et al 14 and moderate risk of bias for Ng et al 16 For cohort studies, the risk of bias for Cappelletti Galante et al, 21 Ng et al 23 and Yew et al 24 is moderate and the risk of bias for Macaione et al 22 is high.…”
Section: Resultsmentioning
confidence: 98%
“…Two cohort studies reported the incidence of rehospitalization. 21 , 22 Macaione et al’s study was divided into four groups ( Figure 5 ) and each subgroup consisted of one-fourth of all patients. Macaione et al 22 2012a depicted omeprazole versus H 2 RAs; Macaione et al 2012b reported esomeprazole versus H 2 RAs; Macaione et al 2012c included results of lansoprazole versus H 2 RAs; and Macaione et al 2012d included results of pantoprazole versus H 2 RAs.…”
Section: Resultsmentioning
confidence: 99%
“…41 A relationship was observed between use of omeprazole and increased risk of severe adverse events, such as development of coronary disorders that might lead to death. 32,39,43,62,88,94,96,101 Regarding the clinical outcomes of the studies, the safety (ADRs and DIs) and the therapeutic ineffectiveness can be correlated.…”
Section: Resultsmentioning
confidence: 99%
“…The frequency of adverse reactions was classified according to the leaflet of the reference drug product, except for the 28 studies for which there was no information on the leaflet. 80 3* 2* 3* Galante et al, 2012 96 4* 1* 3* Lin et al, 2012 81 4* 2* 3* David-Neto et al, 2012 49 4* 1* 3* Soriano et al, 2014 16 4* 2* 3* Chen et al, 2014 28 4* 2* 3* Wang et al, 2017 97 4* 2* 3* Gomm et al, 2016 44 4* 2* 3* Yi et al, 2017 47 4* 2* 3* Varallo et al, 2018 41 4* 2* 3* Imperatore et al, 2018 45 4* 2* 3* Lazzerini et al, 2018 42 4* 1* 3* Li et al, 2018 48 4 Table 3. Continuation Several drug interactions relating to omeprazole, especially with antiplatelet agents, are known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation